Heavy metal content (Cd and Cu) in the flesh and gills of ponyfish (Leiognathus Equulus) in Cilincing coastal waters, Jakarta bay - Tinur Awwali Aliza; Sulistiono; Hariyadi Sigid; Riani Etty; Sinaga Jessica (BIO Web of Conferences)
Cilincing coastal waters, as one of the coastal waters of Jakarta Bay, apart from being a fishing ground for local fishermen, is also a location for various community activities, including residential, industrial, transportation, shipping and tourism. One of the fish resources in the region is ponyfish (Leiognathus equulus). These various community activities can produce waste which has an impact on the fish. This study aims to analyze the heavy metal content in the flesh and gills of ponyfish exposed to heavy metals caught in Cilincing coastal waters, Jakarta Bay. Sampling was carried out for 6 months (February - July 2023). Analysis of heavy metal content in flesh and gills was carried out using Atomic Absorption Spectrophotometer. The content of the heavy metal Cd in flesh and gills exceeds quality standards. In the fish samples, inflammatory cell infiltration was found (in the fish flesh) and there was edema, lamella fusion, basal cell hyperplasia and secondary cell hyperplasia (in the fish gills). Based on calculations, the safe limit for consumption of ponyfish caught in Cilincing waters should be no more than 1.858 kg of flesh/week for adults and 0.558 kg of flesh/week for children.